Needs Analysis for Developing a Constraints-Led Traditional Game to Combat Sedentary Lifestyles in Elementary Students - Nawi Nawi; Bambang Priyono (GLOBAL HEALTH SCIENCE GROUP, 2026)
The global epidemic of sedentary lifestyles and excessive gadget use has severely degraded the physical fitness of elementary school students, specifically their agility and cardiovascular endurance. While traditional games like Gobak Sodor offer motor skill benefits, they often lack precise physiological intensity control and utilize passive elimination systems. This study aims to develop and evaluate